A Genetic Screen for Fission Yeast Gene Deletion Mutants Exhibiting Hypersensitivity to Latrunculin A. Issue 10 (1st October 2016) - Asadi, Farzad; Michalski, Dorothy; Karagiannis, Jim
Abstract: Fission yeast cells treated with low doses of the actin depolymerizing drug, latrunculin A (LatA), delay entry into mitosis via a mechanism that is dependent on both the Clp1p and Rad24p proteins. During this delay, cells remain in a cytokinesis-competent state that is characterized by continuous repair and/or reestablishment of the actomyosin ring. In this manner, cells ensure the faithful completion of the preceding cytokinesis in response to perturbation of the cell division machinery. To uncover other genes with a role in this response, or simply genes with roles in adapting to LatA-induced stress, we carried out a genome-wide screen and identified a group of 38 gene deletion mutants that are hyper-sensitive to the drug. As expected, we found genes affecting cytokinesis and/or the actin cytoskeleton within this set ( ain1, acp2, imp2 ). We also identified genes with roles in histone modification ( tra1, ngg1 ), intracellular transport ( apl5, aps3 ), and glucose-mediated signaling ( git3, git5, git11, pka1, cgs2 ). Importantly, while the identified gene deletion mutants are prone to cytokinesis failure in the presence of LatA, they are nevertheless fully capable of cell division in the absence of the drug. These results indicate that fission yeast cells make use of a diverse set of regulatory modules to counter abnormal cytoskeletal perturbations, and furthermore, that these modules act redundantly to ensure cell survival and proliferation.